Reinforcement of fibrous laminated composite structures using graphene nanoplatelets - Σερέτης, Γεώργιος (Σχολή Μηχανολόγων Μηχανικών, 2018)
The subject of the present Thesis is “Reinforcement of fibrous laminated composite structures using graphene nanoplatelets”. The Thesis’ main language is English, followed by an additional short version in Greek. The reasons for this language selection are two. Primarily, the rendering of key terms of international terminology for this scientific field in Greek is in many cases problematic or even impossible. Therefore, in order to maintain the fidelity of the international terminology, it was necessary to writing the Thesis in English. Also, since the English language is the only official language of all reputable international scientific journals and conferences, it is obvious that the international scientific community is mostly familiar with the use of English language and terminology. Thus, the second objective of the above selection is to facilitate access of the international scientific community to the present Thesis. The research work presented in this thesis is reflected through publications in prestigious international journals and international conferences. It also includes papers that have been submitted for publication in international scientific journals, but the preview process is not completed yet. This Thesis is a synthesis of the above works, bridged together through discussion, annotations and analytical explanations. After the present section, the main body of the Thesis follows in English language. In this part, the reader can find all the research work conducted, together with the required theoretical and analytical background, as well as comparisons with the current literature where required. At the end of each chapter, the literature used is presented. The shortened Greek version can be found at the end of the present manuscript. Thus, the reader will obtain an overview of the materials used, the production/fabrication, control and evaluation of nanoscale materials methods and processes, the computational methods (finite elements analysis, analytical, statistics, etc.), as well as the most important results. All the above is presented analytically in the main body of the Thesis.